PREMENSTRUAL SYNDROME DALAM FOTOGRAFI EKSPRESI - Dio Nanda Baskara (Institut Seni Indonesia Yogyakarta, 2020)
Premenstrual Syndrome is a symptom experienced by women before menstruation arrives. Many stories in the form of complaints from female friends. Based on this, ideas emerged to create photographic works of expression about the effects of Premenstrual Syndrome that were packaged with anaglyph technique. The impact to be visualized is a physical, psychological, and emotional symptom in the period before and until menstruation is over. Premenstrual syndrome information that has been collected through observation will be displayed visually by the medium of photography and using the object of a professional female model, as well as the addition of supporting properties to reinforce the message to be conveyed so as not to develop the meaning that comes out of the ideas that have been made. The work of photography created is a work of expression photography. This creation has an embodiment concept that displays visuals from the development of three-dimensional photographs, namely anaglyph and how to see this work must use anaglyph glasses, in the first glasses using a red colored glass lens and the second glasses using a blue lens glass and then how to view works using these glasses in turn. As for the obstacles that were experienced in the presentation of the embodiment of works including akat, place and time. The place is very influential on the atmosphere that appears in the photo, so the choice of place must be really in accordance with the concept to be appointed.Keywords: Premenstrual Syndrome, anaglyph, fine art photography.